ANALISIS STRATEGI MENGAJAR GURU BAHASA INGGRIS PADA PANDEMI COVID-19 DI SMK SWASTA PEMDA RANTAU PRAPAT TAHUN AJARAN 2020/2021 - Shopiah Anggraini Rambe; Anna Leli Harahap; Muhammad Rusli; Saphril Setia Hadi (Jurnal Education and Development, 2022)
The Analysis of the Teaching Strategy of English Teachers is an analytical study that is useful for knowing the situation or learning process during the Covid-19 pandemic, especially how the teacher's strategies are in learning during this pandemic, especially English teachers. This study uses a qualitative type, generating data through interviews and documentation to obtain the results of the analysis. The object of research is in the Private Vocational School of the Regional Government of Rantauprapat. The research sample is schools by interviewing teachers and several students at the school. The data from this analysis were taken from observation and taken through the instruments of several questions given to the teachers and students who were interviewed, so that accurate analysis results were obtained. Researchers asked questions related to teaching and learning activities at this school, especially with what strategies teachers used in teaching during this pandemic in the learning process.